Exploring Agrotourism Models: Integrating Socio-Economic Diversity in Rural Development - Sadafbek Husanboev (European Science Publishing, 2023)
Agrotourism, a multifaceted concept, demands a nuanced approach considering the varied models for its development. Regional strategies must meticulously incorporate these models, accounting for the unique characteristics of our country, particularly the diversity inherent in regional and local conditions. This article revealed the multifaceted nature of agrotourism. Its role as an economic and development catalyst in regions characterized by socio-economic diversity was studied. This analysis explores the development of agrotourism, emphasizing its pivotal role in addressing economic disparities within rural areas. It examines two distinct models: one where small agricultural entities independently engage in agrotourism activities and another where agrotourism is envisioned as a comprehensive rural enterprise. The study underscores Europe's targeted support for agrotourism in economically challenged regions, highlighting its potential to stimulate income growth and counter rural employment deficiencies.
Keywords: Agrotourism Development, Regional Directions, Diverse Models, Rural Tourism, Socio-Economic Diversity, Local Conditions, Agritourism Concepts, Rural Economy, Tourist Villages, Economic Alternatives.